2020
DOI: 10.1037/dev0000930
|View full text |Cite
|
Sign up to set email alerts
|

Does gender-bending help or hinder friending? The roles of gender and gender similarity in friendship dissolution.

Abstract: We explored how gender and gender similarity affects friendship dissolution following the transition to middle school. We predicted that both gender and gender similarity (measured by perceived similarity to own-gender and other-gender peers) explain dissolution trends and that less own-gender similarity or more other-gender similarity predicts more friendship dissolution. We considered gender and gender similarity at both the individual and dyad level (reflecting the discrepancy between friends). Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Gender differences in self-perceived gender typicality were well-documented in literature both in childhood (Doescher & Sugawara, 1990 ; Egan & Perry, 2001 ; Jewell & Brown, 2014 ; Menon, 2011 ; Menon & Hannah-Fisher, 2019 ; Nielson et al, 2020 ; Smith & Leaper, 2006 ; Tam & Brown, 2020 ; Zosuls et al, 2016 ) and in young adulthood (Andrews et al, 2019 ; DiDonato & Berenbaum, 2013 ; Endendijk et al, 2019 ; Lefkowitz & Zeldow, 2006 ) reporting that females showed more flexible attitudes concerning other-gender similarity compared to males (Andrews et al, 2019 ; DiDonato et al, 2012 ; Endendijk et al, 2019 ; Martin et al, 2012 , 2017a , b ; Zosuls et al, 2016 ). Furthermore, studies have investigated the relationship between gender typicality, well-being, academic achievement, and psychosocial adjustment, taking into account gender differences (Carver et al, 2003 ; DiDonato & Berenbaum, 2013 ; Egan & Perry, 2001 ; Jewell & Brown, 2014 ; Lee & Troop-Gordon, 2011 ; Mehta et al, 2017 ; Menon & Hannah-Fisher, 2019 ; Nielson et al, 2020 ; Ueno & McWilliams, 2010 ; Yavorsky & Buchmann, 2019 ). Literature suggests that feeling typical of one’s own gender relates to more gender-typed attitudes, whereas feeling typical of both genders relates to more egalitarian gender attitudes, both in females and males (Andrews et al, 2019 ; Dinella et al, 2014 ; Endendijk et al, 2019 ).…”
Section: Gender Similarity: Gender and Sexual Orientation Make A Differencementioning
confidence: 82%
See 1 more Smart Citation
“…Gender differences in self-perceived gender typicality were well-documented in literature both in childhood (Doescher & Sugawara, 1990 ; Egan & Perry, 2001 ; Jewell & Brown, 2014 ; Menon, 2011 ; Menon & Hannah-Fisher, 2019 ; Nielson et al, 2020 ; Smith & Leaper, 2006 ; Tam & Brown, 2020 ; Zosuls et al, 2016 ) and in young adulthood (Andrews et al, 2019 ; DiDonato & Berenbaum, 2013 ; Endendijk et al, 2019 ; Lefkowitz & Zeldow, 2006 ) reporting that females showed more flexible attitudes concerning other-gender similarity compared to males (Andrews et al, 2019 ; DiDonato et al, 2012 ; Endendijk et al, 2019 ; Martin et al, 2012 , 2017a , b ; Zosuls et al, 2016 ). Furthermore, studies have investigated the relationship between gender typicality, well-being, academic achievement, and psychosocial adjustment, taking into account gender differences (Carver et al, 2003 ; DiDonato & Berenbaum, 2013 ; Egan & Perry, 2001 ; Jewell & Brown, 2014 ; Lee & Troop-Gordon, 2011 ; Mehta et al, 2017 ; Menon & Hannah-Fisher, 2019 ; Nielson et al, 2020 ; Ueno & McWilliams, 2010 ; Yavorsky & Buchmann, 2019 ). Literature suggests that feeling typical of one’s own gender relates to more gender-typed attitudes, whereas feeling typical of both genders relates to more egalitarian gender attitudes, both in females and males (Andrews et al, 2019 ; Dinella et al, 2014 ; Endendijk et al, 2019 ).…”
Section: Gender Similarity: Gender and Sexual Orientation Make A Differencementioning
confidence: 82%
“…Researchers interested in children’s development have described gender identity as a multidimensional construct in which gender typicality is a central component (Braun & Davidson, 2017 ; Carver et al, 2003 ; DiDonato et al, 2012 ; Egan & Perry, 2001 ; Nielson et al, 2020 ; Pauletti et al, 2017 ; Smith & Leaper, 2006 ; Young & Sweeting, 2004 ). Despite different studies that examined self-perceptions of gender typicality, the ways it has been theorized and investigated differ.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, that is not the case here, as evidenced by the low‐gender similar group. Furthermore, recent research suggests that gender non‐conforming youth are not more likely than conforming youth to lose friendships over time (Nielson et al., 2020). Why the two methods of distinguishing friendships produced different results remains an open question, but the striking difference between total and reciprocated friends for other‐gender similar youth specifically is notable.…”
Section: Discussionmentioning
confidence: 99%
“…In response to peer problems, adolescent girls are more likely to demonstrate prosocial behaviour (e.g., supportive encouragement), whereas boys were found to respond using humour (Rose et al, 2016). Girls' peer relationships have also been found to be more stable than boys and are less likely to deteriorate in middle school samples (Nielson et al, 2020). These findings suggest that boys have more aggressive interaction styles than girls and are more willing to use aggressive and socially risky communicative strategies such as humour and sarcasm with peers (Lazarus et al, 2012;Mewhort-Buist et al, 2020).…”
Section: Gender Differences In Peer Relationshipsmentioning
confidence: 99%